(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The use of pedagogical technologies and various didactic games in order to make the primary school teaching process more effective, to improve the quality of the lesson, to instill in students a love for the motherland and parents, to study and apply them. Uncovering the essence of the lesson by using them in the classroom reveals hidden abilities in students.